Comparison of The Right to Be Forgotten Regulations in Indonesia and European Union Countries - Kaendo, Karen Eklesia Gabriella; Adhari, Ade (RechtIdee, 2025)
The development of digital technology has raised crucial issues related to personal data protection, one of which is related to the right to be forgotten. The European Union has strictly regulated this right through the General Data Protection Regulation (GDPR) since 2018, replacing the previous provisions in Directive 95/46/EC. The GDPR itself regulates the "Right to be Erased" or "Right to be Forgotten," which includes how to Request Erasure, Conditions for Erasure, Obligations of Data Controllers, and Exceptions regarding what matters do not apply to the Right to Erasure. In contrast, Indonesia has only just begun to accommodate this principle through changes to the Electronic Information and Transactions Law (UU ITE) of 2016 and the Personal Data Protection Law (UU PDP) of 2022, although it still faces various implementation challenges. This study aims to compare the legal regulations related to the right to be forgotten between Indonesia and the European Union in order to assess the effectiveness of the available legal protection, as well as encourage the preparation of more adaptive regulations in Indonesia. This study uses a normative legal approach, with a statute approach method that focuses on the study of laws and regulations. The results of the study show that the European Union has a more comprehensive and structured protection system through the GDPR, while Indonesia is still in the early stages of development with limitations in institutional and technical aspects, so it is necessary to strengthen the implementation and consider the application of a similar approach as in the European Union to guarantee the right to personal data effectively.